2020
DOI: 10.1101/2020.07.22.202275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional response modules characterise IL-1β and IL-6 activity in COVID-19

Abstract: Dysregulated IL-1 and IL-6 responses have been implicated in the pathogenesis of severe Coronavirus Disease 2019 (COVID-19). Innovative approaches for evaluating the biological activity of these cytokines in vivo are urgently needed to complement clinical trials of therapeutic targeting of IL-1 and IL-6 in COVID-19. We show that the expression of IL-1 or IL-6 inducible transcriptional signatures (modules) reflects the bioactivity of these cytokines in juvenile idiopathic arthritis (JIA) and rheumatoid arthriti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Indeed, in the very recent study by Abers et al [40] , the IL-1b levels although higher than healthy, did not correlate either at baseline or after serial determinations during the disease process with the severity of COVID-19 and patient mortality. In parallel with the previous study, Bell et al [41] have shown that the elevated expression of IL-1b and IL-6 response modules was a characteristic feature of SARS-CoV-2 infection but was not associated with the disease severity, length of stay or mortality.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Indeed, in the very recent study by Abers et al [40] , the IL-1b levels although higher than healthy, did not correlate either at baseline or after serial determinations during the disease process with the severity of COVID-19 and patient mortality. In parallel with the previous study, Bell et al [41] have shown that the elevated expression of IL-1b and IL-6 response modules was a characteristic feature of SARS-CoV-2 infection but was not associated with the disease severity, length of stay or mortality.…”
Section: Discussionsupporting
confidence: 79%
“…However, in another recent study, TNF-α levels -although increased in patients with SARS-CoV-2 infection compared to healthy- were not associated with disease severity and survival [40] . Moreover, the relative role of abnormal IL-1b responses in the immunopathology of severe COVID-19 remains controversial [ 4 , 5 , 40 , 41 , 42 ]. Indeed, in the very recent study by Abers et al [40] , the IL-1b levels although higher than healthy, did not correlate either at baseline or after serial determinations during the disease process with the severity of COVID-19 and patient mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7D ), using transcriptional modules composed of IL-1β ( fig. S12 and Data File S2 ) ( 34 , 35 ) and IL-6 ( 36 ) inducible genes. Taken together, these data are consistent with a model in which exaggerated Th17 responses at the site of host-pathogen interactions in active TB are driven by recruitment of IL-1β or IL-6 producing monocytes ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, we could not investigate PCT as it was not measured routinely in our CAP cohorts. Future studies should also assess, alongside admission WCC and ΔCRP, the discriminatory capacity of PCT, D-dimers [9,22,31], and other novel biomarkers, such as transcriptional signatures that quantify inflammatory cytokine activity [32] or those that discriminate bacterial from viral infections [33].…”
Section: Discussionmentioning
confidence: 99%